THE DYNAMICS OF MANAGEMENT AND ITS DEVELOPMENT IN UZBEKISTAN - Rakhimova Shakhlo Bakhtiyorovna; Hasanova Mohira Salimjon qizi (Journals Park Publishing, 2025)
In this article, the authors examines the evoluation of management theories from classical to modern management practices and study their application in the context of Uzbekistan’s transition from centralized economy to a market oriented- system. The paper begins with analyzing from the foundational management theories: scientific management, administrative management, bureaucratic management, to the human relation movement, modern management. Then explores contemporary approaches that includes digital transformation and strategic management. The influence of these global management theories to both private and state-owned enterprises in Uzbekistan is analyzed with the focus on challenges and opportunities in adopting modern management practices.
Keywords: Management theory, human relation, centralized, bureaucratic, market oriented-system, modern management, private-sector, state-owned.